Famitinib enhances nasopharyngeal cancer cell radiosensitivity by attenuating radiation-induced phosphorylation of platelet-derived growth factor receptor and c-kit and inhibiting microvessel formation. (2nd September 2015) - Mu, Xiaoqian; Ma, Jia; Zhang, Zhanjie; Zhou, Hongxia; Xu, Shuangbing; Qin, You; Huang, Jing; Yang, Kunyu; Wu, Gang
Abstract : Purpose : Famitinib is a novel tyrosine kinase inhibitor. We investigated the effects of famitinib on the radiosensitivity of human nasopharyngeal carcinoma (NPC) cell radiosensitivity in vitro and in vivo, and explored its possible mechanisms. Materials and methods : Human nasopharyngeal carcinoma cell line (CNE-2) were treated with famitinib and radiation, and analyzed by3-(4, 5-dimethylthaizol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), clonogenic survival assay, and Western blot. A xenograft model using CNE-2 cells was established to analyze the effects of famitinib and radiation on tumor volume and microvessel density (MVD). Results : Famitinib dose-dependently inhibited CNE-2 cells growth and significantly reduced clonogenic survival ( p < 0.05), with a sensitivity enhancement ratio (SER) of 1.45. The tumor inhibition rate of the combined treatment group was 91%, which was significantly higher than the radiation group (35%, p < 0.05) and famitinib group (46%, p < 0.05). Famitinib attenuated radiation-induced phosphorylation of the platelet-derived growth factor receptor (PDGFR) and stem cell factor (c-kit) at 0, 30, 60 min after radiation treatment. Furthermore, radiation combined with famitinib decreased tumor MVD ( p < 0.05). Conclusions : Famitinib significantly increased CNE-2 cell radiosensitivity in vitro and in vivo by attenuating radiation-induced PDGFR and c-kit phosphorylation and by inhibiting microvessel formation.